Hubungan Pengetahuan Ibu Dan Dukungan Suami Terhadap Sikap Relaktasi - Setiasih, Sri; Susanti, Nurmalita Sari; Mursiti, Titi; Octaviani, Dhita Aulia (Midwifery Care Journal, 2024)
The implementation of exclusive breastfeeding for infants from 0 to 6 months old has been recommended by WHO since 2002, but the implementation of exclusive breastfeeding is still relatively low. According to Indonesian health data, the  exclusive breastfeeding rate in Central Java province is only 67.4%,  still lower than the national target of 71.58%  This is a reference for regional authorities, especially health workers in Central Java, to evaluate and develop strategic plans to promote exclusive breastfeeding. One solution to increasing breast milk production is to react. Re-breastfeeding is an attempt to breastfeed again after a long period of cessation of breastfeeding. The purpose of this study was to determine the relationship between mothers' knowledge and husbands' support on attitudes toward breastfeeding. This study was performed in the working area of the Lerep Medical Center using a horizontal method. The study population included mothers who did not exclusively breastfeed their infants and whose infants were 0 to 6 months old. The sampling technique was to sample a total  of 71 respondents. Research results  using the chi-square test show that there is an association between the mother's knowledge and her husband's support with rebirth attitudes with p-value = 0.001.